Konsep Garansi Jual Beli Handphone Dalam Meminimalisir Terjadinya Khiyar Aib - Ananda Anju Pulungan; Junda Harahap; Aminah Lubis (Manivest : Jurnal Manajemen, Ekonomi, Kewirausahaan, dan Investasi, 2023)
This research aims to find out the previous study that the author made, namely "The Concept of Warranty for the Sale and Purchase of Mobile Phones in Minimizing the Occurrence of Disgrace in Sinar Ponsel II Environment IV Sibuhuan Market". This research was conducted at the Sinar Ponsel II Shop, Environment IV, Sibuhuan Market. The object of this research is the Head of the Shop and Employees. The research methodology uses qualitative research. The data used in this research are primary data and secondary data. Data collection techniques through library research and field research. The research study conducted was descriptive analysis. Indicates that the Concept of Buying and Selling Guarantee in Islamic Economics has been implemented at Sinar Ponsel II where in Islamic Economics when a buyer chooses to accept and carry out a buying and selling transaction, it means that he has also accepted and carried out the ijab qabul of the guarantee agreement and is happy with the provisions contained therein in the guarantee letter. The official guarantee is based on the guarantee letter, which is included in the category where a warranty can be claimed, only for internal cellphone problems, what is meant by internal cellphone is those related to the engine. This right of khiyār 'disgrace applies from the moment the buyer finds out about the defect after the contract has taken place, is willing or satisfied with it. goods purchased or vice versa. The results of the research, efforts made to minimize the occurrence of Khiyar Disgrace, namely that shop employees usually in marketing their products must properly convey to buyers what the advantages and disadvantages of the cellphone they want to buy are, try out all the various features on the cellphone, including the camera, speaker , Earphones, chargers, batteries, and the type or brand must also be trustworthy so that in buying and selling transactions there are no defects in the goods being sold.